Shear stress analysis and its effects on cell viability and cell proliferation in drop-on-demand bioprinting. (13th June 2018) - Shi, Jia; Wu, Bin; Li, Shihao; Song, Jinchun; Song, Bin; Lu, Wen F
Abstract: Bioprinting has emerged as a flexible technology in tissue engineering to mimic biological and functional organizational complexity of native tissues. Drop-on-Demand (DoD) bioprinting is one of the most promising technologies currently due to the unique characteristics of high-throughput efficiency and cost-effectiveness. Despite these significant advantages, DoD bioprinting has some drawbacks, including loss of cell viability impacted by shear stress. However, there are only very few studies discussed the variation of shear stress in DoD cell printing and its effects on cell behaviours. In this paper, a CFD simulation model of piezoelectric DoD print-head was developed to study shear stress in the nozzle during printing. Experiments were conducted to study the effect of shear stress on cell viability and cell proliferation. The mathematical model of piezoelectric effect is developed with CFD model to improve the simulation accuracy. Parametric studies on shear stress were also carried out. Simulation results demonstrated that (1) shear stress has a dramatic variation around the nozzle orifice mainly during the rise time and the following dwell time of voltage pulse in the episode; (2) the backflow fluid pushed the fluid entered from the inlet flowing down along the wall, increasing the wall shear stress simultaneously; (3) voltage, viscosity and nozzle diameter have important effects on both values and the effect range of shear stress. With simulation results of shear stress, experiments showed that both cell viability and cell proliferation are decreased with the increase of shear stress, whereby shear stress has a larger influence on cell proliferation than on cell viability. Through the proposed simulation model, the computed shear stress during DoD bioprinting is able to link with engineering characteristics, such as printing parameters, and cell characteristics, such as cell viability and cell proliferation. The simulation model can be used to improve cell viability and cell proliferation through optimizing printing parameters to decrease shear stress in piezoelectric DoD bioprinting.